Efficiency of Long-term Storage at Chilling Temperatures (4 ºC) of Lyophilized Tris Egg Yolk Extender on Frozen Bovine Semen - Rungroekrit, Napak; Kajaysri, Jatuporn; Chapanya, Chullachat (Journal of Mahanakorn Veterinary Medicine, 2020)
The lyophilized extender was proved that it had efficiency to be cryoprotectant for spermatozoa in frozen bovine semen. But its stability after long term storage was in question. This study also was assigned to evaluate the long-term storage (3 months) of lyophilized Tris egg yolk extender at 4 0C by analysis the quality of bovine semen after dilution, equilibration and freezing and compare their parameters of semen in fresh Tris egg yolk extender. Eight Holstein bulls was semen collected that each batch of collection was divided equally into two groups. Control group (n=8) and Treatment group (n=8) were diluted with fresh extender and fresh lyophilized extender of Tris egg yolk, respectively. Optimal sperm concentration was adjusted as 80x106/mL. The semen diluents were further processed for cooling and freezing, after that it would be stored at -196 °C for 24 hours. The sperm motilities of both groups were evaluated in terms of sperm motility, progressive sperm motility, rapid sperm motility using computer assisted semen analysis (CASA) and sperm plasma membrane integrity by hypoosmotic swelling test (HOST). The semen diluents of both groups were analyzed three points such as after semen dilution, equilibration and thawing after freezing. The experiments were repeated for three more times. They were repeated of semen quality analysis that the semen in lyophilized extender after storage at 4 0C in vacuum bottles for 1 month, 2 and 3 months of treatment group were analyzed and compared to the semen in fresh extender of control group. The results showed, the percentages of sperm motility, progressive sperm motility, rapid sperm motility and HOST positive after dilution, equilibration and freezing of semen in fresh extender of control group were not significantly different from those parameters of the semen in fresh, 1-month, 2-months and 3 months storages of lyophilized extenders of treatment group (P>0.05) that the all values of spermatozoa in treatment groups were accepted for good cryoprotectant of these lyophilized extenders in frozen semen. In conclusion, the long-term storage (3 months) of lyophilized Tris egg yolk extender still had good efficiency to preserve the frozen bovine semen quality.